Realizacja uprawnień procesowych dziecka jako pokrzywdzonego w postępowaniu w sprawach o wykroczenia i ich ograniczenia - Tunia, Anna (Studia Prawnoustrojowe, 2019)
The subject of the article is the problem of exercising the rights of the child as a victim in misdemeanor cases. The catalog of the rights of the injured party in misdemeanor cases is essentially convergent – regardless of whether the role is played by an adult or a child. However, in a situation where the victim is a child, the state is obliged to show special care for the protection of his rights resulting from the misdemeanor. The article draws attention above all to the rights of the victim, the implementation of which faces certain restrictions or difficulties. The article contains examples of these restrictions and de lege ferenda postulates regarding the extension of their catalog and the manner of their implementation.